Self Efficacy dan Burnout pada Guru - Varina Citra Palupi; Lena Nessyana Pandjaitan (Keluwih: Jurnal Sosial dan Humaniora, 2022)
Abstract—Teachers play an important role in student achievement and development so teachers are required to perform well in the learning process. In addition, teachers have a variety of tasks that are so heavy that these demands can cause teachers to be vulnerable to burnout. This study aims to find out if there is a relationship between self-efficacy and burnout in teachers. The research subjects (N=107) were teachers at two Bondowoso Vocational Schools with a minimum teaching period of 5 years. Data collection was done using Maslach Burnout Inventory (Maslach & Jackson, 1981) and Teacher Sense of Efficacy Scale (Tschannen-Moran & Woolfolk, 2001). The results of the analysis used spearman values that showed that there is a significant negative relationship (p<0.05) between self-efficacy and burnout with r = -0.398. All three aspects of self-efficacy have significant value but in teacher efficacy for classrom management aspects have the highest contribution with burnout (r = -0.406). Burnout levels in the two SMK have very low values and have a high level of self-efficacy. The level of self-efficacy is related to the low burnout rate in teachers at Bondowoso Vocational High School. Keywords: burnout, teacher’s, self-efficacy Abstrak—Guru memiliki peran penting dalam prestasi dan perkembangan siswa sehingga guru diharuskan untuk memiliki kinerja yang baik dalam proses pembelajaran. Selain itu guru memiliki berbagai tugas yang sangat berat sehingga tuntutan tersebut dapat menyebabkan guru rentan mengalami burnout. Penelitian ini bertujuan untuk mengetahui apakah terdapat hubungan antara self-efficacy dengan burnout pada guru. Subjek penelitian (N=107) adalah guru di dua SMK Bondowoso dengan minimal masa mengajar 5 tahun. Pengumpulan data dilakukan dengan menggunakan Maslach Burnout Inventory (Maslach & Jackson, 1981) dan Teacher Sense of Efficacy Scale (Tschannen-Moran & Woolfolk, 2001). Hasil analisis menggunakan nilai Spearman yang menunjukkan bahwa terdapat hubungan negatif yang signifikan (p<0.05) antara self-efficacy dan burnout dengan r = -0.398. Ketiga aspek self-efficacy memiliki nilai yang signifikan namun pada aspek teacher efficacy for classrom management memiliki kontribusi yang paling tinggi dengan burnout (r = -0.406). Tingkat burnout yang ada di dua SMK memiliki nilai yang sangat rendah dan memiliki tingkat self-efficacy yang tinggi. Tingkat self-efficacy memiliki keterikatan dengan rendahnya tingkat burnout pada guru di SMK Bondowosoara. Kata kunci: burnout, guru, self-efficacy